FRI0058 RHEUMATOID ARTHRITIS IS AN INDEPENDENT RISK FACTOR FOR DEVELOPING INFLUENZA REQUIRING HOSPITAL INPATIENT ADMISSION, COMPARABLE TO OLDER AGE AND GREATER THAN SMOKING, IN A LARGE, SINGLE-CENTRE COHORT. (June 2019) - Liu, Bonnia; Mcmaster, Christopher; Liew, David; Buchanan, Russell
Abstract : Background: RA patients are known to be at increased risk of serious infection(1), particularly for respiratory infections such as influenza which are known to be associated with increased morbidity and mortality(2). Currently RA patients do not have enhanced access to high-dose influenza vaccination in our jurisdiction, despite the reported benefit in RA(3) and enhanced access for patients older than 65 years old. The magnitude of the risk from RA compared to smoking or age greater than 65 years old remains incompletely understood. Objectives: To examine the association of RA, smoking, and age greater than 65 years old with hospital inpatient admissions for influenza. Methods: We examined general medical inpatient admissions in a large tertiary hospital between January 2012 and December 2018. Major confounders (smoking status, age and gender) were selected based on causal inference analysis using a directed acyclic graph. Natural language processing and ICD-10 codes were used to determine the diagnosis of rheumatoid arthritis, smoking status and influenza diagnosis. These variables were used in a multivariable logistic regression analysis. The strength of association was assessed using adjusted odds ratios and associated 95% confidence intervals. Results: We assessed 19, 010 patients with at least one general medical inpatient admission during the study period, of which 495 had at least one admission primarily for influenza (Table 1 ). Within this cohort, there were 3791 patients identified as active smokers and 731 with a history of RA. In the multivariable model, patients with a history of RA were more likely to have at least one admission for influenza (OR 1.65 [1.12 - 2.36]). This risk was comparable to that experienced by patients older than 65 years old in an unadjusted analysis (OR 1.62 [1.29 – 2.04]) and stronger than that experienced by smokers in an unadjusted analysis (OR 1.38 [1.12 - 1.69]). Conclusion: RA patients are at independent risk of influenza leading to a hospital inpatient admission, with a magnitude comparable to that of patients aged over 65 years old and greater than that of smokers. Funding authorities should consider making influenza vaccination available for RA patients in a comparable way to that available to patients aged over 65 years old. References: [1] Listing, J., K. Gerhold, and A. Zink, The risk of infections associated with rheumatoid arthritis, with its comorbidity and treatment. Rheumatology (Oxford), 2013. 52(1): p. 53-61. [2] Blumentals, W.A., et al., Rheumatoid arthritis and the incidence of influenza and influenza-related complications: a retrospective cohort study. BMC Musculoskelet Disord, 2012. 13: p. 158. [3] Colmegna I, Useche M, Rodriguez K, Hudson M, Bernatsky S, Nedjar H, Rahme E, Ward B. Efficacy of High-Dose Versus Standard-Dose Influenza Vaccine in Seropositive Rheumatoid Arthritis Patients [abstract]. Arthritis Rheumatol. 2018; 70 (suppl 10). Disclosure of Interests: None declared